اتفاقية سايكس – بيكو واثرها على السياسة البريطانية تجاه كردستان العراق 1916- 1920 دراسة في الوثائق البريطانية - مهدی, سؤدد كاظم (Sulaimani Journal for Humanities, 2018)
ABSTRACT Longer-term time lapse between the years 1916-1920 of the highlights of the stages that paved the way for the emergence of the Kurdish issue in Iraq, which is located between the holding period Sykes - Picot in 1916 and the beginning of the national rule in October 1920 ,. And characterized this period, two aspects are important: First, it represented the end of an era of conflict between the British political schemes in both London and India, Cairo, and Baghdad about the fate of Iraq's political report, ie, between making it a British colony belonging to the Government of India, and the formation of an Arab and Kurdish nationalist governments under British tutelage. The other side has been the emergence of -aloutnah nationalist movement in Iraq, which culminated with many revolutionary movements, most notably revolted in which Arabs contributed and Kurds alike, led the nationalist movement in the stirring one of the most complex problems in Iraq and the Middle East generally, when Mosul has become a problem, "the first challenge affects the formation of the Iraqi state, the Kurdish nationalist movement, which entered the history of Iraq in the name." Also identified the complex problematic relationship Arabic - Kurdish Mkunyen between the presidents of the components of Iraqi society. British politicians played a key role in Alashkalaha between the central government in Baghdad and Kurdish leaders, when he reneged on Buateke the formation of a Kurdish state, like the nation-states, which have worked on it was founded after the collapse of the Ottoman Empire, Arab, like States, and Armenian, etc., and in parallel, the British commanders have done everything possible diplomatic and political efforts to resolve the issue according to the interests and objectives, without paying attention to any party of Kurdish parties to listen to their demands or opinions in this regard.